Study The Effect Of Different Common Beam Sections Having A Constant Cross Sectional Area On The Critical Buckling Load (University of Thi-Qar Journal for Engineering Sciences, 2014)
A simply supported beam is used to calculate the critical buckling load. A common beam sections with constant cross sectional area are used to analyze the results using ANSYS11 program which gives a good results as comparing with the theoretical equation. The critical buckling load depends on the shape and dimensions of beam section which has constant cross sectional area. It observed that the critical buckling load is higher with a wide range of width for thinner hollow rectangular-section than the thicker section and lower for ( I, T & L-sections). Changing the width or thickness for U & Z-sections gave a small effect on the critical buckling load. Increasing the thickness of hollow circle beam section gives a decreasing in the critical buckling load. The last beam section gives a higher critical buckling load as comparing with solid circle section of the same cross sectional area. The same phenomenon is found for hollow rectangular-section as comparing with the solid section.